Tourism sensemaking strategies to give meaning to experience - Woodside, Arch G. (Advances in culture, tourism and hospitality research ;, 2011)
Accurate and useful assessment of tourism market opportunities, network behavior, and tourism destination management performance requires solid foundations in performance evaluation theory as well as applying metrics covering both sensemaking contexts and outcomes. Advances in Culture, Tourism and Hospitality Research seeks to advance knowledge and sense-making skills in interpreting cultural, organizational, and personal influences relating to tourism and hospitality behaviors.The ten papers in this volume make explicit current tourism assessment practices and look at how such assessments are being conducted and how to go about accomplishing prescribing and applying advanced assessment metrics. With a multi-regional focus that includes Asia, Europe, and North American this volume examines a variety of topics including: using importance-performance analysis to discern cultural differences in image perceptions with application to international visitors to Mauritius; network analysis methods for modelling tourism inter-organizational systems; and tools for overcoming continuing bad performance in tourism destination management.